Enhancing compressive behavior of concrete with novel low-cost hybrid passive confinement including large rupture strain cotton ropes: Experimental findings and a design-oriented model - Panumas Saingam; Qudeer Hussain; Ali Ejaz; Adnan Nawaz; Panuwat Joklad; Kaffayatullah Khan (My University, 2024)
Recent research have highlighted the potential of hybrid confinement, combining high tensile strength fiber-reinforced polymers with large rupture strain confinement. This study presents experimental findings on 64 cylindrical and square-shaped specimens tested under axial compression, introducing a novel hybrid confinement method utilizing low-cost fiberglass chopped strand mat sheets and cotton ropes (COFS confinement). The experimental and analytical results yielded several key conclusions. Firstly, circular specimens exhibited significant peak strength increases in various subgroups, with enhancements ranging from 97.5 % to 285.5 %, and ultimate strain improvements ranging from 588.6 % to 1650.0 %. Similarly, square specimens under COFS confinement also demonstrated notable enhancements in ultimate strength and strain, with increases up to 244.7 % and 1083.0 %, respectively, particularly evident with higher levels of confinement. The influence of cross-sectional shape on compressive strength, strain, and energy dissipation was noted, with COFS confinement notably improving these factors for circular sections. Additionally, the study found that as the unconfined compressive strength increased, the enhancement in compressive strength, ultimate strain, and energy dissipation decreased. Moreover, the confinement ratio positively affected axial behavior improvement, with a proportional enhancement observed. However, the efficacy of the confinement ratio was influenced by cross-section type and plain concrete strength, emphasizing the need for considering these factors in COFS-based confinement design. Lastly, an analytical design-oriented model proposed for approximating stress vs. strain curves of COFS-confined concrete showed close agreement with experimental results, providing valuable insights for future design considerations.
Keywords: Strain (injury); Structural Behavior of Reinforced Concrete